Study Fenomenologi Tentang Faktor-Faktor Yang Mempengaruhi Perawat Terhadap Keberhasilan Pemasangan Intravena Fluid Drip Di Instalasi Gawat Darurat Murni Teguh Memorial Hospital - Nainggolan, Hanna Bulan; Hasibuan, Muhammad Taufik Daniel (Indonesian Trust Nursing Journal, 2024)
Infusion is often called intravenous fluid drip, which is a route for fluid entry through veins. Intravenous fluid drip therapy is an action of administering fluids into the body which functions to replace lost body fluids and correct fluid imbalances in the body. The purpose of this research to find out in depth about the factors that influence nurses on the success of intravenous fluid drip installation in the emergency department of a pure steadfast memorial hospital. This research methods is a qualitative research with a phenomenological study approach. Data collection techniques used in this study were observation, interviews, recording and documentation. The sample used in this study used a purposive sampling technique and was snowball sampling. Participants in this study were 7 nurses who worked in the emergency department at Murni Teguh Memorial Hospital. The results of this research get 3 themes, namely: (1) Knowledge of nurses about intravenous fluid drip, (2) Barriers or obstacles in the installation of intravenous fluid drip, (3) Strategies in overcoming obstacles or obstacles to the installation of intravenous fluid drip, (4) Tips or a trick so that the intravenous fluid drip installation is successful and does not experience repeated punctures. The conclusion of this research is (1) Nurses who work in the Emergency Room are able to explain about intravenous fluid drip well, (2) Nurses know the obstacles or obstacles they often experience when installing intravenous fluid drip, (3) Nurses know what strategies they must do in overcoming obstacles or obstacles that nurses often experience in intravenous fluid drip installation to be successful, (4) Nurses realize that repeated stabbing in intravenous fluid drip installation can lead to complications, so they know anything tips or tricks so that intravenous fluid drip installation is successful and does not experience repeated punctures. Abstrak Infus sering disebut juga dengan Intravena Fluid Drip (IVFD), yang merupakan jalur masuknya cairan melalui pembuluh darah vena. Terapi Intravena Fluid Drip merupakan suatu tindakan dalam pemberian cairan ke dalam tubuh yang berfungsi untuk menggantikan cairan tubuh yang hilang serta memperbaiki ketidakseimbangan cairan di dalam tubuh. Tujuan penelitian ini untuk mengetahui secara mendalam tentang faktor-faktor yang mempengaruhi perawat terhadap keberhasilan pemasangan intravena fluid drip di Instalasi Gawat Darurat Murni Teguh Memorial Hospital. Metode penelitian ini merupakan penelitian kualitatif dengan pendekatan studi fenomenologi. Teknik pengumpulan data dalam penelitian ini adalah observasi, wawancara, rekaman dan dokumentasi. Sampel yang digunakan dalam penelitian ini menggunakan teknik purposive sampling dan bersifat snowball sampling. Partisipan dalam penelitian berjumlah 7 orang perawat yang bekerja di Instalasi Gawat Darurat Murni Teguh Memorial Hospital. Hasil penelitian ini mendapatkan 4 tema yaitu: (1) Pengetahuan perawat tentang intravena fluid drip, (2) Hambatan atau kendala dalam pemasangan intravena fluid drip, (3) Strategi dalam mengatasi hambatan atau kendala pemasangan intravena fluid drip, (4) Tips atau trik agar pemasangan intravena fluid drip berhasil dan tidak mengalami tusukan berulang. Kesimpulan dalam penelitian ini adalah (1) Perawat yang bekerja di Instalasi Gawat Darurat mampu menjelaskan tentang intravena fluid drip dengan baik (2) Perawat mengetahui hambatan atau kendala yang sering mereka alami pada saat pemasangan intravena fluid drip, (3) Perawat mengetahui bagaimana strategi yang mereka harus lakukan dalam mengatasi hambatan atau kendala yang sering dialami perawat dalam pemasangan intravena fluid drip agar berhasil, (4) Perawat menyadari bahwa penusukan berulang dalam pemasangan intravena fluid drip itu dapat mengakibatkan komplikasi, sehingga mereka mengetahui apa-apa saja tips atau trik agar pemasangan intravena fluid drip berhasil dan tidak mengalami tusukan berulang.